Kontribusi BMT NU Ngasem Cabang Senori dalam Transformasi Ekonomi Pedesaan melalui Pendekatan Keuangan Syariah - Mujib, Muhammad Abdul (Journal of Islamic Finance and Syariah Banking, 2025)
This study aims to analyze the contribution of BMT NU Ngasem Senori Branch to strengthening the local economy based on sharia principles, with a focus on the role of BMT in providing access to financing for micro and small business actors and its contribution to the social and spiritual empowerment of the community. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation, and then analyzed inductively to describe the phenomenon of the role of BMT in building a just local economy. The results show that BMT NU Ngasem Senori Branch plays a role not only as a sharia microfinance institution that provides financing without usury through murabahah, mudharabah, and musyarakah contracts, but also as an agent of social transformation that fosters awareness of sharia economics at the grassroots level. The positive impact is seen in the increase in community income, the creation of new jobs, and the development of productive economic activities in the trade, agriculture, and home industry sectors. In addition, the management of zakat, infaq, and alms (ZIS) funds through the Baitul Maal unit plays a role in poverty alleviation, financing the education of orphans, and strengthening social solidarity. The existence of the BMT NU Ngasem Senori Branch has a strategic contribution in realizing a local economy that is inclusive, just, and based on Islamic values.